Letramento em saúde, fragilidade e sintomas depressivos de pacientes com Doença Renal Crônica em Diálise - Silva, Cleanderson Costa da (2025)
Chronic kidney disease (CKD) is a progressive and irreversible condition that has an impact on public health. Its treatment includes conservative approaches and renal replacement therapies, such as dialysis - hemodialysis (HD) or peritoneal dialysis (PD) - and kidney transplantation. Due to the changes caused by the disease, the risk of physical frailty, characterized by a systemic inflammatory process, and social frailty, characterized by reduced support and social relationships, can be present in the patient, intensifying depressive signs and symptoms. In this context, Health Literacy (HL) is essential to enable them to access and understand health information, favoring their decision-making about care, prevention and health promotion, contributing to better adaptation to CKD. The aim of the study was to investigate the association between the level of HL and physical frailty, social frailty and symptoms of depression among HD and PD patients. This is a cross-sectional, descriptive and correlational study with a quantitative approach. 169 HD (N=97) and PD (N=72) patients aged 18 or over were assessed. The instruments used were: Sociodemographic, Economic and Health Conditions Characterization, European Health Literacy Survey Questionnaire Short Form - 16 items (HLS-EU-Q16), Subjective Assessment of Frailty (ASF), Tilburg Frailty Indicator (TFI), HALFT Social Frailty Scale and Patient Health Questionnaire-9 (PHQ-9). The results indicate a predominance of males in HD (51.5%) and females in PD (58.3%). In both treatments, the majority of patients were white, had a steady partner, were retired, took five or more medications and had systemic arterial hypertension. There was a prevalence of problematic/inadequate LS of 39.2% in HD and 43.1% in PD, as well as frailty by TFI (HD=54.6%; PD=84.7%), with a statistically significant difference between the groups (p<0.001). According to the ASF, frailty was 45.4% in HD and 54.2% in PD. Social pre-frailty was identified in both treatments (HD=59.8%; SD=63.9%), as was the presence of depressive symptoms ranging from mild to severe (HD=53.6%; SD=69.4%). There was a moderate positive correlation between LS and family income (r=0.307; p<0.001). Negative correlations of weak magnitude were observed between LS and physical frailty (r=-0.232; p=0.002) and between LS and the social domain of the TFI (r=-0.262; p=0.001). Moderate negative correlations were identified between LS and frailty using the total TFI (r=-0.373; p<0.001), the physical domain of the TFI (r=-0.340; p<0.001), social frailty (r=-0.381; p<0.001) and symptoms of depression (r=-0.301; p<0.001). The logistic regression analysis showed that lower schooling (elementary school - OR=4.544), social frailty (being socially fragile - OR=4.999) and the presence of depressive symptoms (increased severity of depression with each point on the PHQ-9 instrument - OR=1.094) were associated with greater chances of problematic/inadequate SL. It can be concluded that patients' worse SL is associated with low schooling, social frailty and depressive symptoms. Low income and the presence of physical frailty were also associated with worse SL. This information can help health professionals implement more targeted therapeutic interventions, as well as contributing to the development of public policies aimed at this population.